New hard tick (Acari: Ixodidae) reports and detection of Rickettsia in ticks from Sierra Nevada de Santa Marta, Colombia - Oviedo, Ángel (2024)
The Sierra Nevada de Santa Marta (SNSM), located in northern Colombia, is considered a geographical island with high levels of biodiversity and endemism. However, little is known about tick species and their associated microorganisms at the SNSM. In this study we sampled host-seeking ticks in areas of the town of Minca within the SNSM. We collected 47 ticks identified as Amblyomma pacae, Amblyomma longirostre, Amblyomma ovale, Amblyomma mixtum, Haemaphysalis juxtakochi, Ixodes sp. cf. Ixodes affinis and Ixodes sp. Of these ticks, we tested for Rickettsia spp. by amplifying the gltA, SCA1, and 16S rRNA genes via PCR. Rickettsia amblyommatis was detected in one pool of 3 larvae and in a female of A. pacae. Additonally, we isolated Rickettsia sp. belonging to the group of spotted fevers in larvae of A. longirostre. This study reports new findings of six species of ticks and two species of Rickettsia within the SNSM.